2018
DOI: 10.1038/s42003-018-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thylakoid photoprotection can increase yield and canopy radiation use efficiency in rice

Abstract: High sunlight can raise plant growth rates but can potentially cause cellular damage. The likelihood of deleterious effects is lowered by a sophisticated set of photoprotective mechanisms, one of the most important being the controlled dissipation of energy from chlorophyll within photosystem II (PSII) measured as non-photochemical quenching (NPQ). Although ubiquitous, the role of NPQ in plant productivity remains uncertain because it momentarily reduces the quantum efficiency of photosynthesis. Here we used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 62 publications
(110 reference statements)
2
87
0
Order By: Relevance
“…In this article we will focus on the role of NPQ in fast growing annual plants such as cereal crops. NPQ may enhance productivity by limiting damage (photoinhibition) (Hubbart et al , ) but also reduce plant yields by its overly‐protective persistence, lowering quantum yield in low light unnecessarily (Kromdijk et al , ). Such trade‐offs have been discussed previously across wide ecological scales and diverse organisms (Horton, ; Demmig‐Adams and Adams, ; Goss and Lepetit, ; Murchie and Harbinson, ) and create a complex picture that we attempt to address here.…”
Section: Npq Is a Major Plant Eventmentioning
confidence: 99%
See 3 more Smart Citations
“…In this article we will focus on the role of NPQ in fast growing annual plants such as cereal crops. NPQ may enhance productivity by limiting damage (photoinhibition) (Hubbart et al , ) but also reduce plant yields by its overly‐protective persistence, lowering quantum yield in low light unnecessarily (Kromdijk et al , ). Such trade‐offs have been discussed previously across wide ecological scales and diverse organisms (Horton, ; Demmig‐Adams and Adams, ; Goss and Lepetit, ; Murchie and Harbinson, ) and create a complex picture that we attempt to address here.…”
Section: Npq Is a Major Plant Eventmentioning
confidence: 99%
“…Such kinetic properties of NPQ appear to have both a genetic and an environmental influence. Acclimation during growth under fluctuating light, as opposed to static light conditions induces a more rapid engagement of NPQ and in some cases a higher capacity (Demmig‐Adams et al , ; Hubbart et al , ) but not others (Vialet‐Chabrand et al , ). It is clear from genetic alterations in amounts and activities of key players, such as PsbS content and xanthophyll cycle enzymes, that genetic variation exists, as can be seen by comparing contrasting species (Demmig‐Adams et al , ).…”
Section: How Can Npq Determine Leaf Co2 Assimilation Rate?mentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid oxidative stress and photoinhibition, photoprotective mechanisms can be activated in response to high irradiance 58 . There is evidence that photoinhibition has a large impact on biomass production in crops exposed to high light levels 59 and photoprotective mechanisms can increase yield and canopy RUE in rice 60 . Previous studies identified photoprotective genes associated with RUE 22 indicating that protection of photosynthetic machinery has an impact in wheat.…”
Section: Using High Density Genotyping and High-throughput Phenotypinmentioning
confidence: 99%